2010
DOI: 10.1007/s13105-010-0019-5
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of green tea on lead-induced oxidative damage in rat’s blood and brain tissue homogenates

Abstract: Recent studies have shown that lead (Pb) could disrupt tissue prooxidant/antioxidant balance which lead to physiological dysfunction. Natural antioxidants are particularly useful in such situation. Current study was designed to investigate efficacy of green tea extract (GTE), on oxidative status in brain tissue and blood caused by chronic oral Pb administration in rats. Four groups of adult male rats (each 15 rats) were utilized: control group; GTE-group (oral 1.5% w/v GTE for 6 weeks); Pb-group (oral 0.4% lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…These results are consistent with the findings of Badalzahed et al (2008). The increased heart rate in Pb group was probably due to observed central sympathetic nervous system hyperactivity, reduced baroreflex sensitivity and vagal hypotonia in rats treated chronically with lead (Carmignani et al, 2000), while NSO treatment decreased the heart rate to control level and reduced the ST segment significantly; this indicates that NSO has heart rate-reducing effect, which may occur by activating cholinergic mechanisms (El-Tahir et al,1993;Hamed et al, 2010). …”
Section: Discussionmentioning
confidence: 93%
“…These results are consistent with the findings of Badalzahed et al (2008). The increased heart rate in Pb group was probably due to observed central sympathetic nervous system hyperactivity, reduced baroreflex sensitivity and vagal hypotonia in rats treated chronically with lead (Carmignani et al, 2000), while NSO treatment decreased the heart rate to control level and reduced the ST segment significantly; this indicates that NSO has heart rate-reducing effect, which may occur by activating cholinergic mechanisms (El-Tahir et al,1993;Hamed et al, 2010). …”
Section: Discussionmentioning
confidence: 93%
“…Recently, Hamed et al (2010) reported that Pb induced toxicity in different brain areas by interfering on the balance between prooxidant/antioxidant. The authors demonstrated that Pb induced LPO products accumulation, decreased glutathione pool and inhibited antioxidant enzyme activities, such as GST and superoxide dismutase (SOD).…”
Section: Discussionmentioning
confidence: 99%
“…In relation to brain lead levels, results from the present study seemed to correlate with several studies reported to date. A similarly-designed study investigated the effect of green tea leaf extract (GTE) on animals treated with lead acetate 0.4% w/v for six weeks has reported significant decreased in brain and blood levels in the experimantal rats treated with antioxidant compared to non-treated group (Hamed et al 2010). Additionally, the study showed positive correlation between brain lead levels and lipid peroxides (LPO) and negative correlations with glutathione (GSH).…”
Section: Discussionmentioning
confidence: 99%
“…The brain lead concentration was analyzed by atomic absorption spectrophotometer (Perkin-Elmer, United States of America) at 283.3 nm based on a described method with slight modifications (Hamed et al 2010). Brain hemisphere was weighed (1 gm) and placed into a polypropylene tube.…”
Section: Atomic Absorption Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation